Entrepreneurship Culture in Secondary Education in Bisha Province: Reality and Hope - Jalil, Rabah Ramzi Abdul; Mostafa , Safaa Mostafa Darwish; elsadek, Diaaeldin abd elraouf abd elsattar; Shamsan, Eshteak Kaid Said; El-Halim, Naglaa Fathy Ahmed Abd (Journal of Ecohumanism, 2024)
The study aimed to develop a proposed vision for the possibility of spreading the culture of entrepreneurship in secondary education among students in Bisha Governorate. The current study used the descriptive approach, as it is one of the most appropriate research approaches to the nature of the study and its objectives, by presenting previous studies related to the subject of the study, and monitoring the reality of secondary education in Bisha Governorate and the extent of its suitability for the requirements of entrepreneurship (projects). The research reached a set of results and recommendations, which are as follows: Including entrepreneurship education in secondary education through the following areas Mission, vision, objectives and guiding principles: The mission, vision and objectives of secondary education should be clear. And linked to the vision of the Kingdom of Saudi Arabia 2030, and the objectives must be linked to achievable performance indicators in the context of annual or semi-annual objectives , and in order to achieve unified results, a strategy must be adopted. Entrepreneurship Education: A Gradual Model for Integrating Entrepreneurship into Secondary Education The strategy should also highlight the methodology of interventions, i.e. how the implementation of entrepreneurship education will evolve and progress from mere interventions in the curricula to specialized tracks in secondary education , the need to take into account the approved financial budgets and the ability of stakeholders to implement within a realistic time frame , the strategy should also include the funding and budget requirements necessary for its implementation and clarify best practices , and that funding for entrepreneurship education should come from various relevant sources within the country, and there must be an effective communication plan in the strategy aimed at raising awareness about the importance of entrepreneurship education and gaining community support. In addition, the communication and outreach plan should aim to ensure that stakeholders are informed and knowledgeable about specific policies, strategies and initiatives , and the strategy should include monitoring and evaluation methodologies to obtain valuable intelligence and anticipate future strategies and action plans aimed at promoting entrepreneurship education. Therefore, it is essential that the strategy includes short- and long-term key performance indicators and objectives that measure the impact of each intervention as well as monitoring the effectiveness of its implementation by stakeholders.